2013
DOI: 10.1002/art.37805
|View full text |Cite
|
Sign up to set email alerts
|

Type II collagen–specific antibodies induce cartilage damage in mice independent of inflammation

Abstract: Objective. Murine collagen antibody-induced arthritis (CAIA), like collagen-induced arthritis, has clinical and immunopathologic features that parallel those in human rheumatoid arthritis (RA). This study was undertaken to examine the effects of autoantibodies to type II collagen (CII) on articular cartilage in the paws of mice, under conditions in which other factors that may influence joint pathology could be excluded.Methods. Mice of 2 different strains, B10.QC5␦ and the parental strain B10.Q, were injected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 48 publications
(68 reference statements)
2
24
0
Order By: Relevance
“…Investigations by Holmdahl and colleagues have shown that anti-CII can adhere to intact joint cartilage after intraperitoneal or intravenous injection [44,45], but these studies do not explain how such ICs will be in contact with responder cells in the synovial fluid. Studies from Jasin and colleagues indicate that binding of CII antibodies to an intact cartilage surface is dependent on neutrophil elastase-induced damage of the thin layer of small proteins covering the intact joint cartilage [46-48].…”
Section: Discussionmentioning
confidence: 99%
“…Investigations by Holmdahl and colleagues have shown that anti-CII can adhere to intact joint cartilage after intraperitoneal or intravenous injection [44,45], but these studies do not explain how such ICs will be in contact with responder cells in the synovial fluid. Studies from Jasin and colleagues indicate that binding of CII antibodies to an intact cartilage surface is dependent on neutrophil elastase-induced damage of the thin layer of small proteins covering the intact joint cartilage [46-48].…”
Section: Discussionmentioning
confidence: 99%
“…This model replicates many aspects of the human effector phase of RA [21]. It occurs independently of any direct activity of B and T cells, allowing effector processes to be studied independently of the events that occur during disease induction [22]. The articular inflammation and cellular infiltration characteristics of the effector stage are attributable to deposited immune complexes and activation of complement and Fc receptors (FcR) [21,23].…”
Section: Discussionmentioning
confidence: 99%
“…The articular inflammation and cellular infiltration characteristics of the effector stage are attributable to deposited immune complexes and activation of complement and Fc receptors (FcR) [21,23]. Cartilage and bone erosion follows the activation of macrophages, lymphocytes, and synoviocytes and production of MMPs and cytokines [21,22]. …”
Section: Discussionmentioning
confidence: 99%
“…Injection of aCII antibodies is known to trigger a series of pathogenic events, including induction of pain (arthralgia), destabilization of cartilage, infiltration of joints by lymphocytes and proliferation of macrophages [5,[15][16][17]. If labelled mannan is injected together with unlabelled mannan, used at doses that will later trigger inflammation in skin and in joints, the transport of mannan to various tissues will be more efficient.…”
Section: Discussionmentioning
confidence: 99%